Elderly people's experience facing social isolation in the COVID-19 pandemic - Gomes, Maria Alice Cavalcante (2021)
Objective: to unveil the experience of the elderly with social isolation in the pandemic of COVID-19. Methods: qualitative study, with 14 elderlies in social isolation. The content was recorded and processed using the software Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires. Results: six classes were obtained, the first focused on spirituality and pre-pandemic pleasurable activities; the second was related to missing the extra-household routine and family life; the third, to the construction of a new routine; the fourth, to the strategies adopted for the prevention of COVID-19; the fifth, to the signs/symptoms experienced during the infection; and the sixth class, to the fear of dying. Conclusion: the experience of the elderly was permeated by the adaptation of routine, adoption of preventive measures and feelings of anguish in the face of uncertainties.